2014
DOI: 10.1002/oby.20943
|View full text |Cite
|
Sign up to set email alerts
|

Protein and glucose metabolic responses to hyperinsulinemia, hyperglycemia, and hyperaminoacidemia in obese men

Abstract: Objective: In insulin-resistant states, resistance of protein anabolism occurs concurrently with that of glucose, but can be compensated for by abundant amino acid (AA) provision. This effect and its mechanism were sought in obesity. Methods: Pancreatic clamps were performed in 8 lean and 11 obese men, following 5-h postabsorptive, 3-h infusions of octreotide, basal glucagon, and growth hormone, with clamped postprandial-level insulin, glucose, and AA. 048). Increments in muscle S6K1Thr389 phosphorylation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 40 publications
3
35
2
Order By: Relevance
“…However, again the degree of impairment is markedly less than that observed in insulin-stimulated glucose disposal in the same subjects (75,87), suggesting that these different insulin-regulated processes are differentially sensitive to insulin resistance. Similarly, insulin-dependent phosphorylation of FOXO in muscle was unaffected in common insulin resistance (54).…”
Section: Selective Insulin Resistancementioning
confidence: 83%
“…However, again the degree of impairment is markedly less than that observed in insulin-stimulated glucose disposal in the same subjects (75,87), suggesting that these different insulin-regulated processes are differentially sensitive to insulin resistance. Similarly, insulin-dependent phosphorylation of FOXO in muscle was unaffected in common insulin resistance (54).…”
Section: Selective Insulin Resistancementioning
confidence: 83%
“…), but not all (Chevalier et al . ; Hector et al . ), we showed that postprandial myofibrillar protein synthesis rates were stimulated in the CON leg of people with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several studies have reported a reduced stimulation of the muscle protein synthetic response to amino acid provision in obese adults compared to normal weight controls (Guillet et al 2009;Chevalier et al 2015;Murton et al 2015;Beals et al 2016;Smeuninx et al 2017). Interestingly, it appears that this anabolic resistance of postprandial muscle protein synthesis rates in response to exogenous amino acid administration may be confined to distinct muscle protein subfractions (Guillet et al 2009;Chevalier et al 2015;Murton et al 2015;Beals et al 2016Beals et al , 2017. For example, we have recently demonstrated an impairment in the stimulation of postprandial myofibrillar protein synthesis rates (Beals et al 2016) but not mitochondrial protein synthesis rates ) after ingestion of protein-dense food in sedentary obese vs. normal-weight adults.…”
Section: Introductionmentioning
confidence: 99%
“…Obese individuals undergoing a hyperinsulinemic-hyperaminoacidemic-hyperglycemic clamp demonstrated normal protein synthesis and less suppression of breakdown compared with lean subjects, which was associated with lower IRS-1, Akt, and S6K1 phosphorylation (9). It has been proposed that hyperactivation of mTORC1 through S6K1 negatively feeds back to IRS-1, downregulating insulin signaling (73).…”
Section: R859mentioning
confidence: 99%
“…Reduced translation initiation, stemming from dephosphorylated 4E-BP1, reduces protein synthesis (36). Findings ranging from reduced to no difference in skeletal muscle protein synthesis have been reported in obese (9,11,43) and T2D (59, 71) individuals compared with lean individuals. In most cases, individuals diagnosed with T2D are slightly older, which can exacerbate skeletal muscle protein synthesis (10,52) and mass (70).…”
Section: R859mentioning
confidence: 99%